2011
DOI: 10.1148/radiol.10100621
|View full text |Cite
|
Sign up to set email alerts
|

Staging Hepatic Fibrosis: Comparison of Gadoxetate Disodium–enhanced and Diffusion-weighted MR Imaging—Preliminary Observations

Abstract: Gadoxetate disodium-enhanced MR imaging is more reliable for staging hepatic fibrosis than are diffusion-weighted MR imaging, hematologic, and clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(142 citation statements)
references
References 42 publications
5
137
0
Order By: Relevance
“…Several new methods, such as FibroScan, DWI, perfusion, gadoxetic acid-enhanced MRI, and magnetic resonance elastography (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), are increasingly being used to assess liver fibrosis and have shown potential in predicting the severity of liver fibrosis. A previous multicenter prospective study showed that the diagnostic accuracy of FibroScan was high for cirrhosis but poor for significant fibrosis (F≥2) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several new methods, such as FibroScan, DWI, perfusion, gadoxetic acid-enhanced MRI, and magnetic resonance elastography (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), are increasingly being used to assess liver fibrosis and have shown potential in predicting the severity of liver fibrosis. A previous multicenter prospective study showed that the diagnostic accuracy of FibroScan was high for cirrhosis but poor for significant fibrosis (F≥2) (11).…”
Section: Discussionmentioning
confidence: 99%
“…94 For example, because the liver enhancement ratio can, with some correction, be correlated with degree ofˆbrosis, this technique has been used to determine stage of liverˆbrosis. [95][96][97] The ratio of hepatocyte phase enhancement has also been used to assess local hepatic function. 98 Thus, non-morphological or quantitative MR imaging using gadoxetic acid as well as quantitative assessment using diŠusion-weighted and perfusion imaging may represent the new generation of projects.…”
Section: Quantitative Assessment Of Dišuse Liver Diseasementioning
confidence: 99%
“…The diagnostic value of this technique on 1.5T MRI systems has been reported (4)(5)(6)(7)(8)(9). Data on the use of 3T systems in the evaluation of liver fibrosis are scarce (10,11). A higher magnetic field results in a higher signal, permitting higher resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic value of 1.5 Tesla (T) magnetic resonance imaging (MRI) for the detection of parenchymal fibrosis has been published in some reports (4)(5)(6)(7)(8)(9). Only a few reports about the role of 3T MRI for determination of parenchymal fibrosis are present (10,11). There is only one study in the Chinese literature about ADC value changes in liver during nucleoside analogue antiviral treatment in patients with active hepatitis B virus (HBV) (12).…”
mentioning
confidence: 99%